2018
DOI: 10.1111/jcmm.13729
|View full text |Cite
|
Sign up to set email alerts
|

HMQ‐T‐B10 induces human liver cell apoptosis by competitively targeting EphrinB2 and regulating its pathway

Abstract: Hepatocellular carcinoma (HCC) is a highly prevalent cancer worldwide and it is necessary to discover and develop novel preventive strategies and therapeutic approaches for HCC. Herein, we report that EphrinB2 expression is correlated with liver cancer progression. Moreover, by using phosphorylated proteomics array, we reveal a pro‐apoptosis protein whose phosphorylation and activation levels are up‐regulated upon EphrinB2 knockdown. These results suggest that EphrinB2 may act as an anti‐apoptotic protein in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The OD values were measured at 562 nm with a spectrophotometer (Thermo Fisher Scientific Oy, Vantaa, Finland). Percentage of cell viability ratio = [1 − (OD treatment group − OD blank group )/(OD control group − OD blank group )] × 100% [34]. The inhibition rates and IC 50 values were calculated by GraphPad Prism 6.0 and plotted.…”
Section: Methodsmentioning
confidence: 99%
“…The OD values were measured at 562 nm with a spectrophotometer (Thermo Fisher Scientific Oy, Vantaa, Finland). Percentage of cell viability ratio = [1 − (OD treatment group − OD blank group )/(OD control group − OD blank group )] × 100% [34]. The inhibition rates and IC 50 values were calculated by GraphPad Prism 6.0 and plotted.…”
Section: Methodsmentioning
confidence: 99%
“…Percentage of cell viability ratio = [ 1 ( normalO D normalt normalr normale normala normalt normalm normale normaln normalt normalg normalr normalo normalu normalp normalO D normalb normall normala normaln normalk normalg normalr normalo normalu normalp ) / ( normalO D normalc normalo normaln normalt normalr normalo normall normalg normalr normalo normalu normalp normalO D normalb normall normala normaln normalk normalg normalr normalo normalu normalp ) ] × 100 normal% . 20 The inhibition rates and IC 50 values were calculated by GraphPad Prism 6.0 and plotted. According to the results, compound 5 and 7 were selected for further analysis with 3 different times (12, 24, and 48 hours).…”
Section: Methodsmentioning
confidence: 99%
“…Percentage of cell viability ratio = [1(ODtreatment group ODblank group )/(ODcontrol groupODblank group )] × 100% . 20 The inhibition rates and IC 50 values were calculated by GraphPad Prism 6.0 and plotted. According to the results, compound 5 and 7 were selected for further analysis with 3 different times (12,24, and 48 hours).…”
Section: Mtt Assaymentioning
confidence: 99%
“…EphrinB2: The expression of ephrinB2 is linked to the progression of liver cancer. Dai et al [ 53 ] examined the effects of HMQ-T-B10 (B10) on HCC, both in vitro and in vivo. They showed that B10 was able to inhibit the growth of human liver cancer cells by binding to ephrinB2 and suppressing its signaling pathway, which induced apoptosis.…”
Section: The Eph/ephrin Signaling In Hcc—preclinical Datamentioning
confidence: 99%